Effect of Craniofacial Growth Pattern on Head Posture - Kale, Burak; Buyukcavus, Muhammed Hilmi (Journal of Dentistry Indonesia, 2020)
Head posture refers to the upright position of the head of a standing or sitting subject. The literature reports that head posture is affected by many factors. Objective: To evaluate differences in head posture according to craniofacial growth pattern. Methods: A total of 163 individuals (83 females and 80 males) were included in this study. Patients were divided into three groups according to ANB angle as Class I, Class II, and Class III, and each group was divided further into three subgroups according to SN/GoGn angle as hyperdivergent, normodivergent, and hypodivergent. The patients were compared in terms of head posture measurements. Two-way ANOVA was used to evaluate the main and interactive effects of vertical growth pattern and malocclusion type on the head posture of the patients. Results were considered statistically significant at p < 0.05. Results: No statistically significant difference between malocclusion and face-type groups was observed in all head posture measurements (p > 0.05). Conclusion: Head posture is similar among subgroups of different malocclusion types separated by vertical growth pattern.